(untitled) - Nixon, Robin (Sebastopol, CA, 2015)
Build interactive, data-driven websites with the potent combination of open-source technologies and web standards, even if you only have basic HTML knowledge. With this popular hands-on guide, you'll tackle dynamic web programming with the help of today's core technologies: PHP, MySQL, JavaScript, jQuery, CSS, and HTML5.
Keywords: MySQL (Tài nguyên điện tử),MySQL (Electronic resource)